Teaching tools to engage Anishinaabek First Nations women in cervical cancer screening: Report of an educational workshop. (April 2016) - Zehbe, Ingeborg; Wood, Brianne; Wakewich, Pamela; Maar, Marion; Escott, Nicholas; Jumah, Naana; Little, Julian; ,
Objective: To explore educational strategies for engaging First Nations women in Canada to attend cervical cancer screening. Design: Within a participatory action research framework, semi-structured interviews with health-care providers in First Nations communities revealed that education about the value of screening is perceived as being a key factor to promote cervical cancer screening. Setting: To obtain feedback from workshop informants, a 1-day educational workshop was held to identify appropriate educational intervention strategies, which would be applied in a forthcoming randomised controlled cervical screening trial. Methods: Common discussion and discussion groups, which were facilitated by a First Nations workshop moderator and a note taker. Results: This workshop helped to strengthen the ethical space dialogue with the First Nations communities with whom the study team had established research partnerships. The workshop atmosphere was relaxed and the invited informants decided that an educational health promotion event for community women needed to be held prior to inviting them to the cervical screening trial. Such an event would provide an opportunity to communicate the importance of attending regular cervical screening allowing women to make informed decisions about screening participation. Complementary promotional items, including an eye-catching pamphlet and storytelling, were also suggested. Conclusion: The key messages from the events and promotional items can help to de-stigmatise women who develop a type of cancer that is caused by a sexually transmitted virus that affects both men and women. Developing and implementing positive health education that respectfully depicts female bodies, sexuality and health behaviours through a First Nations lens is strongly warranted.